PUBLIC PARTICIPATION GOVERNANCE IN IMPROVING DIGITAL LITERACY FOR THE PREVENTION OF ONLINE GAMBLING IN THE MINISTRY OF RELIGIOUS OF BOJONEGORO REGENCY - Yunita Ramandani; Esa Septian; Ida Swasanti (Journal of Social Politics and Governance (JSPG), 2026)
This study aims to comprehensively analyze the role of the Bojonegoro District Ministry of Religious Affairs in building public participation through strengthening digital literacy based on religious values as an effort to prevent online gambling. The focus of the research problem lies in the low quality of community participation, which is still symbolic and does not yet show active involvement in the planning, implementation, and evaluation of policies. In this context, public participation does not yet fully reflect empowerment but remains at a consultative level without a balanced distribution of power between the government and the community. This study uses Sherry R. Arnstein's Ladder of Citizen Participation Theory to identify the position and dynamics of ongoing participation. The approach used is a qualitative case study with data collection techniques through in-depth interviews, field observations, and documentation analysis. The results of the study show that public participation is still at a tokenistic level, characterized by one-way communication, limited dialogue spaces, and the dominance of top-down policy approaches. Therefore, this study recommends strengthening participatory governance through inclusive dialogue forums, secure and responsive reporting systems, cross-sector collaboration, and the strengthening of digital literacy based on religious values in a sustainable and structured manner.